Assessment of Serum Levels of Vitamin B12 and Folic Acid in Iraqi Patients with Lichen Planus (Medical Forum Monthly, 2025)
Objective: To assess serum levels of vitamin B12 and folic acid in patients with lichen planus.Study Design: Comparative studyPlace and Duration of Study: This study was conducted at the Department of Oral Medicine, College of Dentistry, Uruk University, Iraq from 1st March 2024 to 31st August 2024.Methods: We examined the serum vitamin B12 and serum folate levels of 44 patients who presented with oral/skin and mixed lichen planus. Blood samples were obtained by venipuncture, sera were separated in sterile tube stored frozen until assay, and an Amersham International vitamin B12/folate DUAL radio assay kit was utilized for the purpose of determining the levels of vitamin B12 and folate in human serum.Results: 18.1% of the subjects had low levels of serum vitamin B12 and serum folic acid, which is significantly higher than the 6.3% of the subjects who served as controls and the percentage was not markedly distinct from the control group.Conclusion: Hematological disorders are less likely to increase the risk of developing various types of Lichenplanus.